2020
DOI: 10.1186/s12936-020-03174-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations in the erythrocyte during blood-stage development of the malaria parasite

Abstract: Background: Human blood cells (erythrocytes) serve as hosts for the malaria parasite Plasmodium falciparum during its 48-h intraerythrocytic developmental cycle (IDC). Established in vitro protocols allow for the study of host-parasite interactions during this phase and, in particular, high-resolution metabolomics can provide a window into host-parasite interactions that support parasite development. Methods: Uninfected and parasite-infected erythrocyte cultures were maintained at 2% haematocrit for the durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 79 publications
3
40
0
Order By: Relevance
“…O-positive human RBCs were obtained from healthy blood donors as part of Johns Hopkins University’s phlebotomy protocol (Institutional Review Board protocol number: NA_00019050). Previously described methods were used to deplete white blood cells from the collected blood [ 9 ], and RBCs were maintained in a culture medium that was originally designed to maintain continuous cultures of P. falciparum [ 9 ]. Quadruplicate samples were collected at 0, 8, 16, 24, 32, and 40 h after transfer into fresh culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O-positive human RBCs were obtained from healthy blood donors as part of Johns Hopkins University’s phlebotomy protocol (Institutional Review Board protocol number: NA_00019050). Previously described methods were used to deplete white blood cells from the collected blood [ 9 ], and RBCs were maintained in a culture medium that was originally designed to maintain continuous cultures of P. falciparum [ 9 ]. Quadruplicate samples were collected at 0, 8, 16, 24, 32, and 40 h after transfer into fresh culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…These datasets were included in this analyses because the experiments performed in these studies use methods that are identical to this study and have only minor differences in their culture medium, making these datasets suitable for studying inter-study variations in RBC metabolism. As a perturbation standard, metabolomic data were also analysed from iRBC cultures that were maintained under normal conditions during blood-stage growth [ 9 ]. To ensure the robustness of the analyses, only metabolites with greater than 1000 raw counts at all sampled time points and across all the replicates of uRBC and iRBC cultures were included.…”
Section: Methodsmentioning
confidence: 99%
“…Foundational and novel studies have identified various factors that correlate with an increase in gametocytogenesis. These include, but are not limited to, host immunity Graves et al, 1988;Motard et al, 1995;Buckling et al, 1999), regulation of the key parasite genes GDV1 and AP2-G (Day et al, 1993;Eksi et al, 2012;Brancucci et al, 2014;Coleman et al, 2014;Kafsack et al, 2014;Filarsky et al, 2018;Josling et al, 2020), host lipid and biomolecule biosynthesis and metabolism (Gulati et al, 2015;Brancucci et al, 2017;Tanaka et al, 2019;Tewari et al, 2020), fluctuations in host hormone production (Trager and Gill, 1992;Lingnau et al, 1993), and chemotherapy (Puta and Manyando, 1997;Robert et al, 2000;Tjitra et al, 2002;Hamel et al, 2005;Elbasit et al, 2006;Schneider et al, 2006). Each of these triggers may be altered in the context of a co-morbidity such as HIV-1.…”
Section: Background Overview Of Malaria Parasite Transmissionmentioning
confidence: 99%
“…In the process, Plasmodium produces various by-products including pipecolic acid, a catabolite of lysine ( Fig 1E). Pipecolic acid is detected in in vitro P. falciparum cultures, murine malaria models, and humans with P. falciparum, but not in uninfected RBC cultures or in humans without malaria infection [43][44][45]. Other metabolites potentially generated by the parasite include VOCs pinene and limonene, which may derive from Plasmodium's isoprenoid biosynthetic pathways and are detected in P. falciparum cultures and breath of humans with falciparum malaria [46].…”
Section: Plasmodium-derived Metabolites Identified Using Metabolomicsmentioning
confidence: 99%